A SINFONI integral field spectroscopy survey for galaxy counterparts to damped Lyman α systems – VI. Metallicity and geometry as gas flow probes. Issue 1 (27th January 2016) - Péroux, Céline; Quiret, Samuel; Rahmani, Hadi; Kulkarni, Varsha P.; Epinat, Benoit; Milliard, Bruno; Straka, Lorrie A.; York, Donald G.; Rahmati, Alireza; Contini, Thierry
Abstract: The use of background quasars provides a powerful tool to probe the cool gas in the circumgalactic medium of foreground galaxies. Here, we present new observations with SINFONI and X-Shooter of absorbing-galaxy candidates at z = 0.7–1. We report the detection with both instruments of the Hα emission line of one sub-damped Lyman α (sub-DLA) at z abs = 0.941 87 with $\log N({\rm H}\, {\small {I}})$ = 19.38$^{+0.10}_{-0.15}$ towards SDSS J002133.27+004300.9. We estimate the star formation rate: SFR = 3.6 ± 2.2 M⊙ yr −1 in that system. A detailed kinematic study indicates a dynamical mass M dyn = 10 9.9±0.4 M⊙ and a halo mass M halo = 10 11.9±0.5 M⊙ . In addition, we report the [O ii ] detection with X-Shooter of another DLA at z abs = 0.7402 with $\log N({\rm H}\, {\small {I}})$ = 20.4 ± 0.1 towards Q0052+0041 and an estimated SFR of 5.3 ± 0.7 M⊙ yr −1 . Three other objects are detected in the continuum with X-Shooter but the nature and redshift of two of these objects are unconstrained due to the absence of emission lines, while the third object might be at the redshift of the quasar. We use the objects detected in our whole $N({\rm H}\, {\small {I}})$ -selected SINFONI survey to compute the metallicity difference between the galaxy and the absorbing gas, $δ _{\rm H\, \small {I}}(X)$, where a positive (negative) value indicates infall (outflow). We compare this quantity with the quasar line-of-sight alignment with the galaxy's major (minor) axis, another tracer of infall (outflow). We find that these quantities do not correlate as expected from simple assumptions. Additional observations are necessary to relate these two independent probes of gas flows around galaxies.